Dental care for the bariatric patient. (2nd April 2021) - Hamilton, Jessica; Gittins, Mary; Geddis-Regan, Andrew; Walton, Graham
Abstract : As the overweight and obese population increases, one must be mindful of the implications on the delivery of dental care to this group. Appropriate facilities must be available, which may warrant structural and equipment adaptations to clinical and non-clinical areas. The complexity of dental treatment planning and delivery may be compounded by medical comorbidities, and careful consideration must be given to the suitability and safety of conscious sedation and general anaesthesia in order to facilitate treatment. This article aims to discuss how safe provision and equitable access to dental care can be achieved for the bariatric population. CPD/Clinical Relevance: This article aims to discuss the challenges posed by the increase in the overweight and obese population and considerations to be taken for provision of safe and equitable bariatric dental care.